Is Innate Memory a Double-Edge Sword in Alzheimer's Disease? A Reappraisal of New Concepts and Old Data - Salani, Francesca; Sterbini, Valentina; Sacchinelli, Eleonora; Garramone, Mariagrazia; Bossù, Paola (Frontiers in Immunology, 2019)
An emergent concept in immunology suggests that innate immune system is capable to undergo nonspecific long-term responses and to provide resistance by modifying the reactivity to sequential pathogen challenge. This phenomenon, named innate memory, involves epigenetic and metabolic reprogramming of innate immune cells. Current literature shows that the innate memory process has a mainly beneficial role in host defense, but sometimes can exert detrimental effects, as common in many diseases. Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline and dementia. Accumulating findings demonstrate that inflammation is involved in AD pathogenesis and progression and recent genetic and functional data confirm the driving role of the innate immune component in the disease. Furthermore, AD patients show high burden of the most relevant infectious agents and up-regulation of inflammatory features in their innate immune cells, including an activated or “primed” status of myeloid phagocytic cells in both brain and periphery, resembling trained immunity conditions. Thus, it is conceivable that AD innate cells may be firstly involved in the attempt to resolve recurrent/persistent inflammation but then acquire a trained phenotype mostly unable to maintain the immune regulation, leaving uncontrolled or sometimes supporting the progression of neurodegeneration. The present review aims to summarize evidence evoking innate immune memory mechanisms in AD and to interpret their potential role, either protective or harmful, in disease progression. A better understanding of such mechanisms will provide a fertile ground for development of novel diagnostic and therapeutic pathways in AD cure.